Visualizing interferential stimulation of human brains - Huang, Yu (Frontiers in Human Neuroscience, 2023)
Transcranial electrical stimulation (TES) is limited in focally stimulating deep brain regions, even with optimized stimulation montages. Recently interferential stimulation (IFS), also known as transcranial temporal interference stimulation (TI, TIS, or tTIS), has drawn much attention in the TES community as both computational and experimental studies show that IFS can reach deep brain areas. However, the underlying electrodynamics of IFS is complicated and difficult to visualize. Existing literature only shows static visualization of the interfered electric field induced by IFS. These could result in simplified understanding that there is always one static focal spot between the two pairs of stimulation electrodes. This static visualization can be frequently found in the IFS literature. Here we aim to systematically visualize the entire dynamics of IFS. Following previous work, the lead field was solved for the MNI-152 head, and optimal montages using either two pairs of electrodes or two arrays of electrodes were found to stimulate a deep brain region close to the left striatum with highest possible focality. We then visualized the two stimulating electrical currents injected with similar frequencies. We animated the instant electric field vector at the target and at one exemplary off-target location, in both 3D space and as a 2D Lissajous curve. We finally visualized the distribution of the interfered electric field and the amplitude modulation envelope at an axial slice going through the target location. These two quantities were visualized in two directions: radial-in and posterior-anterior. We hope that with intuitive visualization, this work can contribute as an educational resource to the community’s understanding of IFS as a powerful modality for non-invasive focal deep brain stimulation.